Global research landscape on two coumarin derivatives: A scientometric study of trends and innovations from 1990 to 2022 - Tomi Lois Adetunji; Chijioke Olisah; Ahmed Olatunde; Habibu Tijjani; Mohammad S. Mubarak; Abdur Rauf; Adeyemi Oladapo Aremu (Arabian Journal of Chemistry, 2024)
Daphnetin(7,8-dihydroxycoumarin) and esculin (6,7-dihydroxycoumarin-β-D-glucopyranoside) are natural coumarins that have gained increasing research attention over the years due to their therapeutic applications in a wide range of human ailments. This study assessed the current research status and future research trends of daphnetin and esculin through bibliometric analysis. Relevant articles on these compounds published between 1990 and 2022 were identified in the Web of Science and Scopus databases. “Daphnetin”* or “Esculin”* were used as the search terms to retrieve articles in the “Topic” field of both databases, and RStudio and VOSviewer were used for bibliometric analysis and visualization of meta-data from the retrieved documents. A total of 2172 publications on both compounds were identified. Research outputs on daphnetin and esculin have increased steadily over the years with an annual growth rate of 4.46%. China (576 articles, 28.2%) and USA (198 articles, 9.7%) are the top countries researching on daphnetin and esculin with China being the main country in the international cooperation network. International Journal of Systematic and Evolutionary Microbiology (215 articles), Journal of Clinical Microbiology (71 articles), International Journal of Systematic Bacteriology (29 articles), Archives of Microbiology (24 articles), and Antonie Van Leeuwenhoek (21 articles) are the top five journals publishing articles on these compounds. The most common research topics for both compounds were their biological activities, including anti-microbial, antibiotic resistance, anticancer, anti-inflammatory and antioxidant effects. With an average citation of 21.83 per document, citation analysis revealed that both compounds have been cited a considerable number of times, indicating their significance in the scientific community. Taken together, findings from this review provide insights into the status and trends of daphnetin and esculin research, thus highlighting their increasing interest and potential applications in the medical field.